How Economic Growth Indicators Can Adapt to Weakening Money Growth - Zalwah Ashiffah Lestari; Sanusi Gazali Pane; Dinda Dwi Lestari; Boy Sandi Situmorang (Journal of Management, Economic, and Accounting, 2026)
Economic growth is generally measured using conventional indicators such as Gross Domestic Product (GDP). However, when money supply growth weakens, these indicators are considered less able to represent the overall economic condition. This study aims to examine how economic growth indicators can adapt to conditions of weakening money supply growth. This study used a literature review method by analyzing national and international journals published after 2015 and accessed through Google Scholar. The results of the study indicate that weakening money supply growth affects economic growth slowdown and reduces the effectiveness of conventional economic growth indicators. Therefore, the use of alternative indicators and a multidimensional approach that integrates monetary and financial variables is necessary.